Transnational France - Stovall, Tyler Edward, author.
1 online resource
Keywords: "Now in its second edition, Tyler Stovall's Transnational France takes a transnational approach to the history of modern France that draws the reader into a key aspect of France's political culture: universalism. Beginning with the French Revolution and its aftermath, Stovall traces French history right up into the present day and examines France's relations with three other areas of the world: Europe, the United States and France's colonial empire. The book opens a lens onto both French identity and the history of the world more broadly which allows the reader to engage with French history in a much wider context. This new edition features an additional chapter on France in the Twenty First Century that offers an analysis of current events and issues as seen through historical perspective. Issues addressed include anti-Semitism, Islamophobia, and the gilets jaunes, as well as the impact of Brexit, the maturation of the National Front under Marine LePen, and the administration of Emmanuel Macron. Giving a global view of France's history, this is the perfect volume for students of Modern France and French history courses"--